A cytochemical approach to describe oocyte development in the freshwater ostariophysan, Serrasalmus maculatus (Characiformes) - Quagio-Grassiotto, Irani [UNESP]; Wildner, Daniel Dantas [UNESP]; Dias Guimaraes-Bassoli, Arlene Cristina (Elsevier B.V., 2014)
With the intent to provide additional information on the reproductive biology of the ostariophysian fish, the oocyte development in Serrasalmus maculatus is here described under light and electron microscopy by using some cytochemical methods. Our results are discussed considering the cellular processes that drive the oocyte development and comparing to the available information on other groups of fish. Despite the oocyte development to be in general a conserved process, some characteristics of the oocytes of this species come to light. Possibly related to the reproductive strategy of S. maculatus are the absence of oil droplets and the presence of well-developed cortical alveoli. Besides this finding, our results suggest the presence of high content of basic residues in yolk proteins, the presence of acidic polysaccharides in the zona pellucida and a possible involvement of the follicular cells in the steroidogenesis process. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Ostariophysi; Characiformes; Oocyte development